Discrimination among Ethnic Minorities Groups in Singapore - Imam Subchi; Siti Amsariah; Ahmad Bachmid (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2021)
This article analyzed the state of Singapore as a multiracial country and how Singapore issued regulations to harmonize life between different ethnicities in its society. This research used Systematic Literature Review (SLR) that allowed collecting relevant evidence on the given topic that fits the pre-specified eligibility criteria and have an answer for the formulated research questions. Data search was performed by searching the internet using databases such as Google Scholar, J store, Research Gate, Sage Journal, and Scientific Electronic Library Online (SciELO). The data source used in this research was the publication of the last 10 years. Some of the articles reviewed included minorities against Muslims, against ethnic minorities who were left behind in education and economics, and against people who failed to carry out the culture in the country of Singapore. These findings are largely consistent with the Singapore constitution, meaning that the Singaporean government provides equal treatment to all citizens. Article 152 of the Constitution of the Republic of Singapore guarantees the rights of minority communities to their religious belief and practice. However, in everyday life, there is discrimination against minorities, especially in terms of religion, culture, and social education. This research suggests enriching future research by obtaining interviews or direct questionnaires to minorities who live in Singapore.